Viral Marketing dan Asosiasi Brand dengan Boneka Labubu - Diorra Calysta Wijaya; Miracle Angel Yosie Rogi (ManBiz: Journal of Management and Business, 2025)
This research explores the impact of viral marketing and brand associations that leverage the Labubu doll as a promotional tool. Many brands capitalize on the doll’s popularity to attract consumers, making it a fascinating case study for marketing strategies. Using a qualitative approach, this study gathered data through a Focus Group Discussion (FGD) with six participants who have relevant experience in the topic. The findings highlight that marketing strategies, particularly the "tebus murah" (redeem at a low price) promotion by Bittersweet by Najla, significantly drive consumer interest. Consumers are not only drawn to the affordability but also to the exclusivity of such promotions. Additionally, viral marketing campaigns in cafes have further amplified the doll’s desirability, turning it into a collectible item. The sense of urgency created by limited-time offers and interactive in-store promotions enhances consumer engagement, making them more likely to purchase. These strategies suggest that direct consumer interaction with the product, combined with attractive promotional deals, plays a crucial role in increasing consumer interest and purchase intention. As a result, brands that effectively integrate viral marketing with exclusive promotions can create a strong emotional connection with their audience, ultimately driving sales and brand loyalty. Keywords: Brand Associations, FGD, Viral Marketing